Improving early childhood development in rural Ghana through scalable low-cost community-run play schemes: Baseline report - Salifu Amadu; Orazio P. Attanasio; Bet Caeyers; Sarah Cattan; Lina Cardona Sosa; Sonya Krutikova; Peter Leighton; Lise Masselus; Mubarik Yakubu (Institute for Fiscal Studies (IFS), 2018)
This report presents a detailed overview of the baseline data collection activities as part of the project "Improving early childhood development in rural Ghana through scalable low-cost community-run play schemes''. The project is collaboration between The Institute for Fiscal Studies (UK), Lively Minds (UK, Ghana) and Innovations for Poverty Action (Ghana), and is funded by the Jacobs Foundation and Global Innovation Fund (GIF). The intervention is implemented by award-winning charity Lively Minds, and targets those in kindergarten in rural Northern Ghana, aged 4 and 5. It focuses on unlocking the potential of caregivers, both volunteer mothers and teachers, training and empowering them with the knowledge, skills and confidence to run educational Play Schemes within kindergarten and provide better care and stimulation at home, using local materials. A key feature of the programme is its scalability; it is low cost and requires only locally available human and physical resources and infrastructure for implementation. Having developed, trialled and refined the programme content and training materials, Lively Minds are focusing on adapting implementation to a model in which the Ghana Education Service (GES) and teachers themselves take key roles in ensuring the success of the programme. The Institute for Fiscal Studies (IFS) has partnered with Innovations for Poverty Action in Ghana (IPA) to implement a rigorous evaluation of the impact of the Lively Minds programme. The evidence provided by this evaluation will be crucial for determining whether there is value in mainstreaming the programme across Ghana and replicating it in other countries. Further, we aim to generate evidence which will contribute more broadly to the state of knowledge on the development and scaling of ECCE interventions in low-income remote rural contexts.
Keywords: 330